Energetic, entropic and economic analysis of an open-air, open-water humidification dehumidification desalination system with a packing bed dehumidifier. (1st November 2019) - He, W.F.; Chen, J.J.; Han, D.; Luo, L.T.; Wang, X.C.; Zhang, Q.Y.; Yao, S.Y.
Highlights: Open-air, open-water configurations are introduced into the HD desalination method. Energetic, entropic and economic analysis for the HD desalination system is conducted. Influences from the effectiveness on the desalination performance are focused. Performance comparison between the current and previous systems are collected. Abstract: In the present paper, an open-air, open-water configuration is introduced into the humidification dehumidification desalination system, to recover the industrial waste heat. Thermodynamic performance, from the energetic and entropic standpoints, and the relevant economic performance of the desalination system are acquired. The theoretical analysis shows that top water production, gained-output-ratio and specific energy consumption reach 96.45 kg h −1, 1.70 and 0.38 kWh kg −1, respectively, while the lowest investment and cost of water production arrive at 848.86$ and 8.04 × 10 −3 $ kg −1 . It is concluded that the thermodynamic performance and cost of water production for the desalination system will benefit, once the humidification and dehumidification effectiveness rise, while the bottom investment is found at a lower humidification effectiveness. Furthermore, the performance comparison between the newly proposed and previous solar and heat pump powered desalination systems confirms the economic advantages.